Clima laboral en el Grupo Ronquillo Sandoya en la ciudad de Babahoyo periodo 2021. - Choez Reyes, Gabriela Alexandra (2022)
In the present case study, we seek to know the work environment of the Ronquillo Sandoya group company located in the city of Babahoyo, which is an administrative factor that intervenes in the performance of companies, which adjusts to the line of investigation used. In this type of research, having as a central problem the various conflicts and discrepancies between work collaborators, for this purpose, it was inquired with various authors taken from bibliographic sources and with qualitative methodology of a descriptive type with a technique based on a survey to know the work environment of this business and thus determine the reality and verifying the importance that this has had.